Gambaran Pengetahuan Remaja Tentang Penyakit Hiv/Aids - Juniwati Barus, Darwita; Henny Arwina B; Desy Lustiyani Rajagukguk (Universitas Sari Mutiara Indonesia, 2024)
HIV/AIDS is a disease that continues to grow and becomes a global health problem in both developed and developing countries. The number of cases of HIV/AIDS in adolescents has increased, where adolescents are a group at risk for HIV/AIDS transmission. High social mobility of adolescents causes social, cultural, cultural, and physical and psychological changes. As a result, adolescents have a high vulnerability to transmission of various types of diseases, especially HIV/AIDS. Good knowledge about the disease will help adolescents to make efforts to prevent HIV/AIDS. The purpose of this study was to describe the knowledge of adolescents about HIV/AIDS in SMP Madya Utama Medan. This research method is a research with quantitative approach with descriptive type and cross sectional design. The sampling technique used was purposive sampling. The sample in this study were students of class VIII and IX SMP Madya Utama Medan, as many as 45 respondents. The statistical test used is a univariate test which produces a variable frequency distribution. Data collection by using a knowledge questionnaire. The results showed that from 45 respondents, 34 respondents (53.33%) had less knowledge about HIV/AIDS, 12 respondents (26,67%) had good knowledge and 9 respondents (20,0 %) had sufficient knowledge. Most teenagers have less knowledge about HIV/AIDS, so it is necessary to increase knowledge through the provision of health education related to HIV/AIDS and its prevention.